(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the role of linguoculturology in the formation and development of tourism terminology based on a comprehensive scientific approach. Tourism terminology is examined as a product of the interaction between language and culture, and its semantic, pragmatic, and cognitive features are revealed. The factors influencing the formation of terms, their national-cultural characteristics, and their importance in global communication are substantiated. In addition, the theoretical and practical aspects of developing tourism terminology based on a linguoculturological approach are scientifically discussed.